2016
DOI: 10.5897/jyfr2015.0164
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Candida albicans strains from South Africa for the production of gliotoxin and other cytotoxic secondary metabolites

Abstract: Candida species cause superficial mycosis and more serious systemic infections. The virulence factors of Candida are their adherence and hyphae formation ability and the production of hydrolytic enzymes. In addition, they produce secondary metabolites which are also implicated in the pathogenesis. Literature on the production of gliotoxin, one of the metabolites by Candida spp. is controversial. The aim of this study was to examine production of gliotoxin and related secondary metabolites by C. albicans strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
(26 reference statements)
0
5
1
1
Order By: Relevance
“…A study achieved by [45], which looked at C. albicans isolates obtained from the oral cavity of patients with oral thrush, revealed that all tested isolates of C. albicans were produced to GT at concentrations ranging between 0.02 and 1.5 µg/ml. But is contradictory to the study achieved by [26,46], which reported that there is no mycotoxin gliotoxin produced in culture medium using various clinically and commensal isolates of C. albicans, C. tropical, C. glabrata, C. kefyr, etc. The correlation between mycotoxin gliotoxin production and virulence in Candida spp.…”
Section: Discussioncontrasting
confidence: 59%
“…A study achieved by [45], which looked at C. albicans isolates obtained from the oral cavity of patients with oral thrush, revealed that all tested isolates of C. albicans were produced to GT at concentrations ranging between 0.02 and 1.5 µg/ml. But is contradictory to the study achieved by [26,46], which reported that there is no mycotoxin gliotoxin produced in culture medium using various clinically and commensal isolates of C. albicans, C. tropical, C. glabrata, C. kefyr, etc. The correlation between mycotoxin gliotoxin production and virulence in Candida spp.…”
Section: Discussioncontrasting
confidence: 59%
“…Of note, gliotoxin was also found to be produced by Candida spp. , including Candida albicans , even though there are conflicting reports on this subject ( Bertling et al., 2010 ; Kosalec et al., 2008 ; Kupfahl et al., 2007 ; Shah and Larsen, 1991 ; Shah et al., 1995 ; Tshabalala et al., 2016 ). To investigate whether Mɸs can sense fungal metabolites present in the fluids absorbed by epithelial cells, we infused fungi-depleted C57BL/6J mice with a hypotonic solution containing or not containing gliotoxin ( Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, this fungi metabolite was shown to induce apoptosis in epithelial cells (Upperman et al, 2003) and to be produced by both pathobionts and food spoilage fungi such as Penicillium chrysogenum (Ismaiel and Papenbrock, 2015;Lewis et al, 2005), which is abundant in the murine intestinal tract (Wheeler et al, 2016). Of note, gliotoxin was also found to be produced by Candida spp., including Candida albicans, even though there are ll OPEN ACCESS Cell 183, 411-428, October 15, 2020 419 Article conflicting reports on this subject (Bertling et al, 2010;Kosalec et al, 2008;Kupfahl et al, 2007;Shah and Larsen, 1991;Shah et al, 1995;Tshabalala et al, 2016). To investigate whether Mɸs can sense fungal metabolites present in the fluids absorbed by epithelial cells, we infused fungi-depleted C57BL/6J mice with a hypotonic solution containing or not containing gliotoxin (Figure 6A).…”
Section: Mɸs Protect Epithelial Cells From Being Poisoned By Fungal Toxinsmentioning
confidence: 99%
“…It should be noted that gliotoxin was also produced by Candida spp. including Candida albicans, although there are conflicting studies on this [32,33]. To determine whether Mφs can detect fungal metabolites in fluids taken up by epithelial cells, we infused fungus-depleted C57BL/6J mice with a hypotonic solution containing or not gliotoxin (Figure 3D, adapted from [20]).…”
Section: Mφs Protect Epithelial Cells From Poisoning By Fungal Toxinsmentioning
confidence: 99%
“…En effet, il a été démontré que ce métabolite fongique induisait l'apoptose des cellules épithéliales [8] et pouvait être produit à la fois par des pathobiontes et des champignons d'altération des aliments tels que Penicillium chrysogenum [31], qui est abondant dans le tractus intestinal murin [26]. Il convient de noter que la gliotoxine était également produite par Candida spp., y compris Candida albicans, même s'il existe des études contradictoires à ce sujet [32,33]. Pour déterminer si les Mφ peuvent détecter les métabolites fongiques présents dans les fluides absorbés par les cellules épithéliales, nous avons infusé des souris C57BL/6J appauvries en champignons avec une solution hypotonique contenant ou non de la gliotoxine (Figure 3D, adapted from [20]).…”
Section: Les Mφ Protègent Les Cellules éPithéliales Contre L'empoisonnement Par Les Toxines Fongiquesunclassified